The endoplasmic reticulum membrane protein Sec62 as potential therapeutic target in SEC62 overexpressing tumors - Zimmermann, Julia S. M.; Linxweiler, Johannes; Radosa, Julia C.; Linxweiler, Maximilian; Zimmermann, Richard (Frontiers in Physiology, 2022)
The human SEC62 gene is located on chromosome 3q, was characterized as a tumor driver gene and is found to be overexpressed in an ever-growing number of tumors, particularly those with 3q26 amplification. Where analyzed, SEC62 overexpression was associated with poor prognosis. Sec62 protein is a membrane protein of the endoplasmic reticulum (ER) and has functions in ER protein import, ER-phagy and -in cooperation with the cytosolic protein calmodulin- the maintenance of cellular calcium homeostasis. Various human tumors show SEC62 overexpression in immunohistochemistry and corresponding cell lines confirm this phenomenon in western blots and immunofluorescence. Furthermore, these tumor cells are characterized by increased stress tolerance and migratory as well as invasive potential, three hallmarks of cancer cells. Strikingly, plasmid-driven overexpression of SEC62 in non-SEC62 overexpressing cells introduces the same three hallmarks of cancer into the transfected cells. Depletion of Sec62 from either type of SEC62 overexpressing tumor cells by treatment with SEC62-targeting siRNAs leads to reduced stress tolerance and reduced migratory as well as invasive potential. Where tested, treatment of SEC62 overexpressing tumor cells with the small molecule/calmodulin antagonist trifluoperazine (TFP) phenocopied the effect of SEC62-targeting siRNAs. Recently, first phase II clinical trials with the prodrug mipsagargin/G202, which targets cellular calcium homeostasis in prostate cells as well as neovascular tissue in various tumors were started. According to experiments with tumor cell lines, however, SEC62 overexpressing tumor cells may be less responsive or resistant against such treatment. Therefore, murine tumor models for tumor growth or metastasis were evaluated with respect to their responsiveness to treatment with a mipsagargin analog (thapsigargin), or TFP, which had previously been in clinical use for the treatment of schizophrenia, or with the combination of both drugs. So far, no additive effect of the two drugs was observed but TFP had an inhibitory effect on tumor growth and metastatic potential in the models. Here, we review the state of affairs.